Neuroprotective role of Fisetin in Alzheimer's disease: An overview of potential mechanism and clinical findings - Fardin Nabizadeh (Neurology Letters, 2024)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder marked by cognitive decline, predominantly due to the accumulation of amyloid-beta plaques and tau neurofibrillary tangles. Despite extensive research, effective treatments remain limited to symptomatic relief. Fisetin, a naturally occurring flavonoid found in fruits and vegetables, has emerged as a promising neuroprotective agent. Its multifaceted mechanisms, including antioxidant, anti-inflammatory, and signaling pathway modulation, suggest potential for AD intervention. Fisetin's ability to inhibit amyloid-beta aggregation, promote peptide clearance, and reduce tau hyperphosphorylation positions it as a viable therapeutic candidate. Additionally, fisetin enhances synaptic plasticity and cognitive function by modulating key signaling pathways such as ERK and CREB. Preclinical studies demonstrate fisetin's efficacy in reducing amyloid-beta and tau pathology, improving cognitive performance, and mitigating oxidative stress and neuroinflammation. Early clinical trials indicate fisetin's safety and potential cognitive benefits in individuals with mild cognitive impairment. To fully realize fisetin's therapeutic potential, further large-scale clinical trials, mechanistic studies, combination therapy explorations, and personalized medicine approaches are essential. Optimizing fisetin's bioavailability and delivery methods, along with long-term safety assessments, will be critical in translating preclinical successes into clinical applications. Fisetin's diverse neuroprotective actions highlight its promise as a multi-targeted approach to AD treatment, offering hope for effective therapeutic strategies against this devastating disease.